The prognostic effect of smoking status on intensively treated acute myeloid leukaemia – A Danish nationwide cohort study. (21st April 2020) - Kristensen, Daniel; Nielsen, Lars B.; Roug, Anne S.; Kristensen, Tove‐Christina C.; El‐Galaly, Tarec C.; Nørgaard, Jan M.; Marcher, Claus W.; Schöllkopf, Claudia; Theilgaard‐Mönch, Kim; Severinsen, Marianne T.
Summary: With rising life expectancy, the importance of patient‐related prognostic factors and how to integrate such data into clinical decision‐making becomes increasingly important. The aim of this study was to evaluate the prognostic impact of smoking status in patients with acute myeloid leukaemia (AML) treated with intensive chemotherapy. We conducted a nationwide cohort study based on data obtained from the Danish National Leukaemia Registry (DNLR). The study comprised Danish patients aged 18–75 years, diagnosed with AML between 1 January 2000 and 31 December 2012. Medical records were reviewed and data on smoking status were collected. A total of 1040 patients (median age 59 years) were included, and 602 patients (58·9%) were categorised as ever‐smokers and the remaining as never‐smokers. Kaplan–Meier survival estimates revealed that ever‐smokers had a significant shorter median overall survival (OS) at 17·2 months [95% CI (14·9;19·1)] compared to never‐smokers at 24·5 months (95% CI [19·2;30·7]). Multivariate analysis revealed smoking status as a significant prognostic factor for inferior OS with a hazard ratio (HR) of 1·22 [95% CI (1·04;1·44)]. In conclusion, smoking status was found to be associated with inferior OS in intensively treated AML patients.